Insight Into the Dynamics of the Ixodes ricinus Nymphal Midgut Proteome - Kozelková, Tereza; Dyčka, Filip; Lu, Stephen; Urbanová, Veronika; Frantová, Helena; Sojka, Daniel; Šíma, Radek; Horn, Martin; Perner, Jan; Kopáček, Petr (Molecular & cellular proteomics, 2023)
Ticks are ectoparasites that feed on blood and have an impressive ability to consume and process enormous amounts of host blood, allowing extremely long periods of starvation between blood meals. The central role in the parasitic lifestyle of ticks is played by the midgut. This organ efficiently stores and digests ingested blood and serves as the primary interface for the transmission of tick-borne pathogens. In this study, we used a label-free quantitative approach to perform a novel dynamic proteomic analysis of the midgut of Ixodesricinus nymphs, covering their development from unfed to pre-molt stages. We identified 1534 I. ricinus-specific proteins with a relatively low proportion of host proteins. This proteome dataset, which was carefully examined by manual scrutiny, allowed precise annotation of proteins important for blood meal processing and their dynamic changes during nymphal ontogeny. We focused on midgut molecules related to lipid hydrolysis, storage, and transport, opening a yet unexplored avenue for studying lipid metabolism in ticks. Further dynamic profiling of the tick's multi-enzyme digestive network, protease inhibitors, enzymes involved in redox homeostasis and detoxification, antimicrobial peptides, and proteins responsible for midgut colonization by Borrelia spirochetes promises to uncover new targets for targeting tick nymphs, the most critical life stage for transmission the pathogens that cause tick-borne diseases.
Keywords: Borrelia; ticks; proteases; midgut; lipid metabolism; Proteomics; protease inhibitors; proteome; klíště; antimicrobial peptides; Ixodes; Proteome; proteom; zvířata; Animals; label-free quantification; Digestive System; trávicí systém; proteomika